Identifikasi Senyawa Fitokimia pada Daun Kersen (Muntingia calabura Linn.) dan Uji Toksisitasnya Terhadap Larva Udang Artemia salina Leach - Kolambani, Ade Febrianto Umbu Romu; Sritamin, Made; Wijaya, I Nyoman (Nandur, 2021)
Singapore cherry ( Muntingia calabura L.) is a plant that has shady trees, is often used as a shade and is easy to grow in various places. All parts of the cherry plant, including roots, bark, fruit, and leaves, contain secondary metabolites that can be used as traditional medicine. The purpose of this study was to determine the phytochemical compounds contained in cherry leaf extract and to determine the level of acute toxicity (LC 50 ) using the Brine Shrimp Lethality Test (BSLT) method. Identification of phytochemical compounds was carried out by gas chromatography-mass spectrometry and acute toxicity test (LC 50 ) was carried out using the BSLT method using the shrimp larvae test insect Artemia salina Leach. The acute toxicity test (LC 50 ) consisted of 6 concentration treatments, namely 500 ppm, 250 ppm, 150 ppm, 100 ppm, 50 ppm, along with negative controls, each of which was repeated three times. The LC 50 value is obtained from probit analysis in Microsoft Office Excel. There are 3 groups of bioactive compounds with the highest peak area in singapore cherry leaf extract, namely groups of flavonoids, phenols, and alkaloid. The result of acute toxicity test (LC 50 ) of singapore cherry leaves extract was 84,029 ppm.